Promoting sustainable agriculture in Devdaha Municipality, Nepal: leveraging agroforestry to address challenges and enhance food security - Sailesh Ranjitkar; Mohammad Ayub; Ukesh Raj Bhuju; Nani Maiya Sujakhu (Circular Agricultural Systems)
Ensuring food security through sustainable agriculture is critical for achieving the Sustainable Development Goals (SDGs). This study aimed to examine farming practices, assess the marketability of agricultural products, and propose interventions to promote sustainable agriculture in Devdaha Municipality, Nepal, with a focus on overcoming gender disparities. Utilizing purposive sampling, interviews, focus group discussions, expert consultations, and direct observations followed by mixed methods analysis, farming practices were examined, the marketability of agricultural products were assessed, and interventions for improvement were proposed. Analysis revealed a diverse range of farm products, identified key challenges limiting profitability (e.g., seasonal variations, market access), and highlighted the need for targeted interventions. Diversifying production towards high-profit crops like mango, banana, papaya, ginger, and turmeric integrated into agroforestry systems was identified as a potential strategy to increase farmer incomes and livelihoods. Findings revealed that cheaper imports contributed to a decline in local production, making efficient marketing systems and gender-sensitive interventions crucial to reverse this trend and empower women's participation in commercial agriculture. The study recommends establishing well-managed local farmers' markets, implementing agricultural subsidies, and launching campaigns to promote indigenous crops to reduce import dependency and boost incomes. Additionally, promoting suitable agroforestry combinations like mango-Moringa-vegetables intercropping can enhance sustainability. By informing on localized strategies aligned with SDG 2, this study offers policymakers potential pathways to strengthen sustainable agriculture, food security, and gender equity in Nepal's rural municipalities.